Divergent seasonal dynamics of high-resolution phosphorus speciation in sediment porewater of small estuaries - Yeran Yin; Hanchang Zhou; Yurui Li; Zheng Wang; Kai Xiao; Zhanrong Guo; Feng Pan; Bojie Fu (Journal of Hydrology, 2026)

TET2 aggravates podocyte mitotic catastrophe and renal injury in diabetic nephropathy via m5C-dependent downregulation of Wee1 and activation of CDK1-cyclinB1 signaling - Jie Feng; Hongjuan Dong; Yi Yang; Liyi Xie; Wanhong Lu; Yurui Guo; Ranran Kong (Inflammation Research, 2026)

Effects of salinity on speciation and mobility of potentially toxic elements in soil porewater of estuarine wetlands - Zheng Wang; Yurui Li; Hanchang Zhou; Chao Li; Yu Cai; Kai Xiao; Zhanrong Guo; Feng Pan (CATENA, 2026)

Contrasting mobility of phosphorus and arsenic in sediments of small estuaries: Insight into high-resolution profiles and seasonal variation - Jiahui Hu; Hanchang Zhou; Zheng Wang; Yurui Li; Kai Xiao; Zhanrong Guo; Feng Pan (Marine Pollution Bulletin, 2026)

Isolation of reassortant H5N1 and H5N8 avian influenza viruses from co-infections and their host-dependent replication dynamics - Yuwei Wu; Nuo Xu; Zhifan Li; Zijun Lu; Yurui Dong; Yijie Guo; Ying Bian; Kunlin Li; Chenzhi Huo; Tao Qin; Sujuan Chen; Hui Yang; et al. (Veterinary Microbiology, 2026)

Fluid evolution in the Naxi Fe polymetallic deposit, Eastern Kunlun, China: Insights from in-situ trace element and sulfur isotope compositions of pyrite and pyrrhotite - Rongqiang Guo; Shijiong Han; Chenggang Cao; Kaizhang Shi; Yurui Yuan; Mingyu Tang; Jinxin Yuan; Yongkun Fang; Yushan Jia (Journal of Asian Earth Sciences, 2026)

A pH/ROS dual-responsive hydrogel enabling a therapeutic trinity of anti-oxidation, anti-inflammation & anti-fibrosis for myocardial infarction repair - Jiao Zhou; Lingbing Zou; Zi Ye; Weiwei Jiang; Jianyu Zheng; Yurui Deng; Linhong Sun; Beibei Guo; Sizhen Wang; Feifei Dong; Feng Yang (Chemical Engineering Journal, 2026)

Effects of extreme heat on vegetation carbon sequestration in the Yellow River Basin - Guanpeng Dong; Yuchen Guo; Hongjuan Zhang; Yansui Liu; Yurui Li; Han Zhang; Junting Zhong (Science China Earth Sciences, 2025)

Oxidizing agents alter surface reaction pathways in heterogeneous Fenton reactions: Surface electron transfer interactions and altered bond breaking processes in contaminants - Yurui Li; Haoran Wu; Bing Yang; Chao Zhu; Shijie Zhou; Lili Ma; Lingli Li; Mingyan Chen; Heng Guo; Yucheng Liu (Journal of Environmental Chemical Engineering, 2025)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

TIC-driven sustainable land use mode in the Loess Plateau: A case study of gully land consolidation project in Yan'an City, China - Yanjun Guo; Yansui Liu; Ruotong Li; Yurui Li; Jieyong Wang (Land Use Policy, 2024)

Pruning and quantization algorithm with applications in memristor-based convolutional neural network - Mei Guo; Yurui Sun; Yongliang Zhu; Mingqiao Han; Gang Dou; Shiping Wen (Cognitive Neurodynamics, 2024)

High resolution dissolved heavy metals in sediment porewater of a small estuary: Distribution, mobilization and migration - Yurui Li; Zheng Wang; Yu Cai; Kai Xiao; Zhanrong Guo; Feng Pan (Science of The Total Environment, 2023)

Coastal aquaculture regulates phosphorus cycling in estuarine wetlands: Mobilization, kinetic resupply, and source-sink process - Kai Xiao; Feng Pan; Yurui Li; Zhenyang Li; Hailong Li; Zhanrong Guo; Xinhong Wang; Chunmiao Zheng (Water Research, 2023)

Unraveling the microbial succession during the natural fermentation of grass carp and their correlation with volatile flavor formation - Naiyong Xiao; Huiya Xu; Yun Hu; Yurui Zhang; Quanyou Guo; Wenzheng Shi (Food Research International, 2023)

A Simplified Panel Method (sPM) for Hydrodynamics of Air Cushion Assisted Platforms - Fengmei Jing; Song Wang; Zhiqun Guo; Yurui Ni (Journal of Marine Science and Engineering, 2022)
Air-cushion-assisted platforms (ACAPs) are floating platforms supported by both buoyancy pontoon and air cushion, which have merits of wave bending moment reduction, better stability, and hydrodynamic performance. However, there is barely a concise method that can quickly predict the motion response of ACAPs. In this paper, a simplified panel method (sPM) was presented for evaluating the hydrodynamics of ACAPs. The sPM extends the conventional boundary integral equation (BIE) to include the radiation solutions of pulsating air pressure but ignores some unimportant air-water cross terms in motion equations whose coefficients cannot be directly derived from conventional Green’s function methods. The effectiveness of the sPM was validated by experimental data from an ACAP model with one air chamber and analytical results from an oscillating water column (OWC). The numerical results demonstrate that the sPM can give desirable predictions for motion responses of the ACAP and inner pressure of the OWC as compared with results from the literature, which suggests the sPM could be approximately applied to evaluation of hydrodynamic performance of ACAPs and OWCs.

Improved in vitro Vitis vinifera L. embryo development of F1 progeny of ‘Delight’ × ‘Ruby seedless’ using putrescine and marker-assisted selection - Tiemei Li; Zhiqian Li; Xiao Yin; Yurui Guo; Yuejin Wang; Yan Xu (In Vitro Cellular & Developmental Biology - Plant, 2018)

GIS-based effect assessment of soil erosion before and after gully land consolidation: A case study of Wangjiagou project region, Loess Plateau - Yansui Liu; Yanjun Guo; Yurui Li; Yuheng Li (Chinese Geographical Science, 2015)